Echocardiographic assessment of the heart in metabolic syndrome complicated with hearth rhythm disorders - E. D. Dzhishambaev (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To study parameters of heart pumping function and left ventricle (LV) geometry in metabolic syndrome patients (MS) depending on the heart rhythm disorders (RD)Material and methods. Totally, 208 men with MS studied, age 35-55 y.o. All patients underwent registration of standard electrocardiogram, veloergometry, ambulatory electrocardiogram monitoring, single- or bidimensional echocardiograpy.Results. In MS patients with combinational RD there was slight asymmetry of the LV, due to significant increase of interventricular septum thickness. In patients with ventricular extrasystoly — same grade of interventricular septum thickening, as of back wall of LV, with the appearance of borderline myocardial mass of LV. In addition, it was found, that in asymmetric remodelling there are mostly supraventricular RD develop, and in significant hypertrophy of LV — supra- and ventricular RD.Conclusion. LV remodelling and development of borderline myocardial mass is one of the causes for cardiac rhythm disorders in MS patients.